Low electron emission yield electrodeposited silver coating for electron multipacting mitigation - Belfio, Julie; Lazar, Florica; Belhaj, Mohamed; Jbara, Omar (Surfaces and Interfaces, 2023)
The phenomenon of electron emission is a detrimental factor to many devices in vacuum high power microwave components used in space communication payloads. This phenomenon is the main mechanism for triggering and sustaining the multipactor effect. One interesting and well used strategy to mitigate the multipactor effect is the production of microwave devices walls with low electron emission yield. The most microwave components of spacecrafts are silver-plated. In order to reduce the total electron emission yield (TEEY), the electrodeposition of surface coatings as an alternative to various frequently advocated methods is reported. In this work, silver coatings were deposited by pulse electrodeposition on a nickel substrate from cyanide-free electrolyte. This approach leads to a good adhesion of the coating on the substrate and to a roughness of the silver deposit allowing to significantly reduce the total electron emission yield. The proposed electrodeposition protocol shows that the maximum value of total electron emission yield (TEEYmax) of the silver decreases from 2.23 to 1.62 and the first cross energy, Ec1, (i.e. energy at which the TEEY is first equal to one) increases from 27 to 46 eV. Ultimately, the surface treatment proposed in this work has great potential to mitigate the multipactor phenomenon in silver plated microwave components.
Keywords: Electrodeposition; Electron emission yield; Particles morphology; Multipactor; Roughness; Silver coatings